Peningkatan Hasil Belajar Materi Pertumbuhan Ilmu Pengetahuan Bani Abbasiyah Melalui Metode Paired Story Telling dan Media Articulate storyline - Anisa Mudrikah Zain; Guntur Cahyono (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study was to improve cognitive learning outcomes for students of class VIII D SMP Dharma Lestari on the material for the pertumbuhan ilmu pengetahuan pada masa Bani Abbasiyah period by applying the paired story telling method and media articulate storyline. This type of research uses classroom artion research (CAR) with data obtained by the method of observation, tests and documentation. The results showed an icrease in student learning outcomes which can be seen from the average class in the first cycle of 77,91 with a completeness percentage of 77%, the class average in the second cyle of 88,26 with a completeness percentage of 88%. So, it can be concluded that by applying the paired story telling method and media articulate storyline, it can improve the learning outcomes of class VIII D students, of Dharma Lestari middle school, salatiga.